Identification of mithramycin analogs with improved targeting of the EWS-FLI1 transcription factor - Osgood, Christy L (Clin Cancer Res, 2016)
PURPOSE: The goal of this study was to identify second-generation mithramycin analogs that better target the EWS-FLI1 transcription factor for Ewing sarcoma. We previously established mithramycin as an EWS-FLI1 inhibitor, but the compound’s toxicity prevented its use at effective concentrations in patients. EXPERIMENTAL DESIGN: We screened a panel of mithralogs to establish their ability to inhibit EWS-FLI1 in Ewing sarcoma. We compared the IC(50) to the maximum tolerated dose established in mice to determine the relationship between efficacy and toxicity. We confirmed the suppression of EWS-FLI1 at the promoter, mRNA, gene signature, and protein levels. We established an improved therapeutic window by using time-lapse microscopy to model the effects on cellular proliferation in Ewing sarcoma cells relative to HepG2 control cells. Finally, we established an improved therapeutic window using a xenograft model of Ewing sarcoma. RESULTS: EC-8105 was found to be the most potent analog and was able to suppress EWS-FLI1 activity at concentrations nontoxic to other cell types. EC-8042 was substantially less toxic than mithramycin in multiple species but maintained suppression of EWS-FLI1 at similar concentrations. Both compounds markedly suppressed Ewing sarcoma xenograft growth and inhibited EWS-FLI1 in vivo. CONCLUSIONS: These results provide a basis for the continued development of EC-8042 and EC-8105 as EWS-FLI1 inhibitors for the clinic.